Doubly Charged Lepton Search Potential of the FCC-Based Energy-Frontier Electron-Proton Colliders - A. Ozansoy (Advances in High Energy Physics)
We search for the doubly charged leptons (L−−) predicted in composite models including extended weak isospin multiplets, namely, IW=1 and IW=3/2, at the Future Circular Collider- (FCC-) based energy-frontier electron-proton colliders with the center-of-mass energies of s=3.46 TeV, s=10 TeV, and s=31.6 TeV, respectively. We deal with the e−p⟶L−−X⟶e−W−X process, calculate the production cross sections, and give the normalized transverse momentum and pseudorapidity distributions of final-state electron to obtain the kinematical cuts for the discovery. We show the statistical significance (SS) of the expected signal yield as a function of doubly charged lepton mass (SS−ML plots) to attain the doubly charged lepton discovery mass limits for both the IW=1 and IW=3/2. It is obtained that discovery mass limits on the mass of doubly charged lepton for IW=1 (IW=3/2) are 2.21 2.73 TeV, 5.46 8.47 TeV, and 12.9 20.0 TeV for s=3.46 TeV, s=10 TeV, and s=31.6 TeV, respectively.